USING MAKE A MATCH TECHNIQUE IN TEACHING DESCRIPTIVE TEXT TO THE SEVENTH GRADE STUDENTS OF SMP NEGERI 2 LUBUKLINGGAU - Eka Fitriana; Ardayati; Syafitri, Dewi (ELite Journal : International Journal of Education, Language and Literature, 2023)
The problem of this research was to answer whether it was significantly effective or not to use Make a Match technique in teaching Descriptive Text to the Seventh Grade Students of SMP Negeri 2 Lubuklinggau in the Academic Year 2022/2023. In addition, the objective in conducting this research was to find out the effectiveness of this technique in teaching descriptive text. Here, quasi-experimental research with total population 417 students was used by the researcher. Then, the researcher used cluster random sampling included 71 students from class VII.5 and VII.6. From the investigation which had been done by the researcher, it was found out that tobtained was 5.473 which was higher than ttable 1.667. It can be concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Finally, there was a significant difference achievement between students who were taught and were not taught by using Make a Match technique.